The evolutionary relationships of marine hatchetfishes (Stomiiformes: Sternoptychidae) based on genomic and morphological data - May, Zachary A.; Smith, W. Leo; Davis, Matthew P. (Zootaxa, 2026)
The dragonfishes and allies (Stomiiformes) are among the most species rich and ecologically important clades of deep-sea fishes. Within the Stomiiformes, the marine hatchetfishes (Sternoptychidae) are the second largest family with 10 genera and 79 species. Sternoptychids are well known for their highly reflective bodies and bioluminescent photophores that are hypothesized to aid camouflage and allow communication with conspecifics in the deep sea. While sternoptychids in Argyropelecus, Polyipnus, and Sternoptyx have anteriorly deep and posteriorly shallow bodies that resemble a hatchet or an ax in lateral view, the seven other sternoptychid genera have a more uniform, slender body; these differences have been used to separate these clades into two subfamilies. Despite their ecological importance and captivating life history, the phylogeny of this group has not been studied as extensively as other deep-sea fish groups. To date, phylogenetic studies have primarily used morphological characters to examine sternoptychid evolutionary relationships, and, perhaps surprisingly, prior molecular studies with sufficient genus-level sampling have never recovered the family as monophyletic. Herein, we investigate the evolutionary relationships of the Sternoptychidae using 415 mitochondrial and nuclear loci (including ultraconserved elements [UCEs]) and 149 morphological characters. We present the results of concatenated and species-tree molecular analyses and combined phylogenetic analysis. Based on these results, we provide a revised monophyletic classification that recognizes a monophyletic Sternoptychidae without any subfamilies because our results recovered a paraphyletic Sternoptychinae and a polyphyletic Maurolicinae. Specifically, our combined analyses revealed that the slender-bodied species in Maurolicus were nested within the traditionally recognized deeper-bodied sternoptychines (Argyropelecus, Polyipnus, and Sternoptyx). This four-genus clade was found sister to a slender-bodied clade composed of Araiophos, Argyripnus, Danaphos, Sonoda, Thorophos, and Valenciennellus. Unlike previous molecular analyses, all genera that included more than one species in our analyses were recovered as monophyletic. Our revised sternoptychid phylogeny provides a comprehensive framework for subsequent researchers interested in exploring evolutionary scenarios for the marine hatchetfishes.